Integration of the Use of Digital Technology in the PKN Learning Process in the Era of the COVID-19 Pandemic - Aulia Utami Putri; Gatot Budiarto; Ermanovida Ermanovida; Syarifuddin Syarifuddin; Retna Mahriani (Budapest International Research and Critics University, 2022)
This research aims to provide an analysis of the use of digital technology in the PKN learning process in the era of the COVID-19 Pandemic as well as what factors are supporting and inhibiting lecturers in the online learning process for PKN course lecturers. This research uses qualitative methods through a descriptive approach. The data collection techniques used in this study are in the form of interviews, questionnaires or questionnaires, and documentation. The type of interview used in this study was a semistructured interview. The type of questionnaire used in this study is an open questionnaire and problem analysis is done through interviews to the coordinators of PKN courses, PKN lecturers, and students. There is a major problem in the integration of digital technology, namely the need to strengthen digital technology in PKN learning so as to reduce the obstacles felt by students and lecturers such as signal constraints, server down, do not have supporting infrastructure facilities such as laptops and handphone and increase the creativity and innovation of lecturers in teaching using digital technology so that lessons do not cause saturation of students with the materials provided and solutions provided to increase the content and activities of e-learning, facilitating lecturers' subjects for the learning process.